Is early exposure to cannabis associated with bipolar disorder? Results from a Finnish birth cohort study - Denissoff Alexander; Mustonen Antti; Alakokkare Anni-Emilia; Scott James G; Sami Musa B; Miettunen Jouko; Niemelä Solja (WILEY, 2025)
Background and aims: There are few longitudinal studies assessing the association of cannabis use and subsequent onset of bipolar disorder. We aimed to measure the association between early cannabis exposure and subsequent bipolar disorder.
Design, setting and participants: Observational study linking a sample from the northern Finland birth cohort 1986 (n = 6325) to nation-wide register data to examine the association of life-time cannabis exposure at age 15/16 years and subsequent bipolar disorder until age 33 (until the end of 2018); 6325 individuals (48.8% males) were included in the analysis.
Measurements: Cannabis exposure was measured via self-report. Bipolar disorder was measured via bipolar disorder-related diagnostic codes (ICD-10: F30.xx, F31.xx) collected from the Care Register for Health Care 2001-18, the Register of Primary Health Care Visits 2011-18, the medication reimbursement register of the Social Insurance Institution of Finland 2001-05 and the disability pensions of the Finnish Center for Pensions 2001-16. Potential confounders included demographic characteristics, parental psychiatric disorders, emotional and behavioral problems and other substance use.
Findings: Three hundred and fifty-two adolescents (5.6%) reported any cannabis use until the age of 15-16 years. Of the whole sample, 66 (1.0%) were diagnosed with bipolar disorder. Adolescent cannabis use was associated with bipolar disorder [hazard ratio (HR) = 3.46; 95% confidence interval (CI) = 1.81-6.61]. This association remained statistically significant after adjusting for sex, family structure and parental psychiatric disorders (HR = 3.00; 95% CI = 1.47-6.13) and after further adjusting for adolescent emotional and behavioral problems (HR = 2.34; 95% CI = 1.11-4.94). Further adjustments for frequent alcohol intoxications, daily smoking and lifetime illicit drug use attenuated the associations to statistically non-significant.
Conclusions: In Finland, the positive association between early cannabis exposure and subsequent development of bipolar disorder appears to be confounded by other substance use.